2018
DOI: 10.1002/dmrr.2981
|View full text |Cite
|
Sign up to set email alerts
|

When metformin is not enough: Pros and cons of SGLT2 and DPP‐4 inhibitors as a second line therapy

Abstract: The newer oral therapies for type 2 diabetes mellitus, dipeptidyl peptidase-4 (DPP-4) inhibitors and sodium glucose cotransporter 2 (SGLT2) inhibitors, have advantages over older agents. Dipeptidyl peptidase-4 inhibitors are weight neutral and have few adverse effects. Sodium glucose cotransporter 2 inhibitors have additional benefits: weight loss, blood pressure reduction, cardiovascular risk reduction, and renoprotective effects. Sodium glucose cotransporter 2 inhibitors have increased risk of urogenital inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 120 publications
(262 reference statements)
1
16
0
3
Order By: Relevance
“…DDP4 or SGLT2 inhibitors) [ 12 ]. Avogaro et al [ 52 ] showed in a meta-analysis of DPP4 inhibitors an apparently accepted mean increase in HbA 1c of 0.22% after 52 weeks of usage. Long-term loss of glycaemic control of 0.30% over 4 years of treatment was observed with dapagliflozin [ 53 ].…”
Section: Rationale For Timely Insulin Treatmentmentioning
confidence: 99%
“…DDP4 or SGLT2 inhibitors) [ 12 ]. Avogaro et al [ 52 ] showed in a meta-analysis of DPP4 inhibitors an apparently accepted mean increase in HbA 1c of 0.22% after 52 weeks of usage. Long-term loss of glycaemic control of 0.30% over 4 years of treatment was observed with dapagliflozin [ 53 ].…”
Section: Rationale For Timely Insulin Treatmentmentioning
confidence: 99%
“…Considering their complementary physiological pathways, the combination of incretin‐based agents may prevent the rise in EGP and thus improve the hypoglycemic efficacy. Recent studies have confirmed a favourable role of these new classes of oral therapies over the conventional hypoglycemic agents in the treatment of T2DM and suggested a pleiotropic benefit when they were used in combination . What is more, each drug class has specific adverse effect (AE) profiles, and their combination has the potential to change respective side effect profiles or to mitigate or cause additive AEs, which still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, GLP‐1RAs and SGLT‐2 inhibitors have a different adverse event profile . Most of these events are infrequent, but yet they were significantly greater in the treatment groups compared to the placebo ones.…”
Section: Direct Evidences For New Anti‐diabetic Drugs Against CV Diseasementioning
confidence: 99%